Merging Two Façade Types into a New Product: Glass Sandwich Panel - M. Teich (Challenging Glass Conference, 2016)
Developed by seele for industrial and commercial buildings, iconic skin glass sandwich panel (GSP) is a novel glass panel façade that meets high-level design and economic demands. The idea is to merge two established façade products into a new one: The glass sandwich panel consists of an outer printed glass sheet bonded to a standard sandwich panel. This creates a glass exterior in the form of panels up to a height of 15 m. These huge formats allow architects to employ glass sandwich panels to create homogeneous and flush façade surfaces in glass. This paper discusses the structural testing and numerical verification of the glass sandwich panel with a main focus on the silicone bonding between glass and sandwich. Furthermore, an outlook is given how to integrate window and door elements flush with the façade surface.